MEWUJUDKAN KETERATURAN PEMBUATAN BENDA UJI PENGUJIAN UTAMA MELALUI PENGUJIAN PRA KONDISI - Sabaruddin, Sabaruddin; Tjarong, M. Wihardi; Ali, Nur; Djamaluddin, Rudy (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
In general, the study emphasizes the importance of reliability and validity, including quantitative research (focus on post-positivism view). Reliability of a study of which can be determined by the appropriate selection of ingredients / materials and treatment of substance / material chosen, where one of the important things is that there is regularity in the manufacture of test specimens for their designated purpose. Preparation of the test object to the given will result in research that is not biased either on empirical research, manuals, analytical and validation with the program, which of course is the methodological side. While on the theoretical side of course is expected to occur before the development of the theory. It could even happen that the new theory and methodology.